Nanocrystalline Ag-doped cobalt oxide as a flexible electrode material for high performance supercapacitor application. (February 2023) - Jadhav, Sarika; Kalubarme, Ramchandra; Chauhan, Ratna; Singh, Anar; Kale, Bharat; Ashokkumar, Muthupandian; Gosavi, Suresh
Abstract: Co3-x Agx O4 (x = 0 ~ –0.4) nanocomposite with a spherical shape and porous surface has been synthesized using a simple, fast and scalable combustion method. The highly stable Ag-doped Co3 O4 nanocomposite particles were found to be 20‐–50 nm in size with high surface area, crystallinity, and porosity. The specific capacitance value of the Co2.7 Ag0.3 O4 (CA3 ) electrode was observed to be higher than other electrodes. Doping of Ag provides a large Ag/Co3 O4 interface which enhanced the electrical conductivity of the electrode by moulding ohmic contact. This contributes to a stable and straight passage for rapid charge transfer. The calculated specific capacitance value of CA3 nanocomposite was 648 F g ‐ −1 at a current density of 0.25A g ‐ −1 which was 6-fold greater than the undoped Co3 O4 and 2‐–4-fold greater than Ag-doped Co3 O4 nanocomposites prepared at other concentrations. The electrodes exhibited excellent cyclic stability with capacitance retention of 93% after 10, 000 cycles having an energy density of 88.23 Wh kg ‐ −1 at 1.75 kW kg ‐ −1 power density indicating a promising material for supercapacitor application. Fabricated symmetric solid-state flexible device of Ag-doped Co3 O4 also demonstrated reliable charge storage performance with a maximum energy density. The theoretical study also revealed that Ag doping into Co3 O4 introduces additional localized states around the fermi level, between the highest occupied states and lowest unoccupied states. The presence of higher localized states near the Fermi level and smaller bandgap than Co3 O4 enhanced the specific capacitance of the system, providing support to the experimental observation on improvement in energy charge storage. Graphical abstract: A flexible supercapacitor device of Ag doped Co3 O4 nanocomposite synthesized by coumbation method demonstrate maximum energy density 39.3 Wh kg ‐ −1 at a power density of 0.75 kW kg ‐ −1 . Unlabelled Image Highlights: Successfully synthesized spherical-shape Ag doped Co3 O4 having particle size 20-50 nm by combustion method The Co2.7 Ag0.3 O4 (CA3 ) sample exhibit specific capacitance of 648 F g -1 at 0.25 A g -1 Ag-doped Co3 O4 shows superior cycling stability (92.7 %) over 3000 cycles Solid-state flexible supercapacitor device, demonstrates a maximum energy density of 39.3 Wh kg -1 at a power density of 0.75 kW kg -1 Additional localized states around the Fermi level are introduced due to doping which acts as centers for redox reaction and subsequently enhances the capacitance.